Моделювання жирнокислотного складу січених напівфабрикатів з м’яса птиці з використанням модифікованих жирів - Шведюк, Дмитро Анатолійович; Пасічний, Василь Миколайович; Радзієвська, Ірина Геронтіївна (НТУ "ХПІ", 2017)
Досліджено можливість покращення біологічної повноцінності жирнокислотного складу напівфабрикатів м’ясних на основі м’яса курчат бройлерів шляхом введення до рецептур модифікованого жиру та комбінування м’ясної сировини з клітковиною та рослинною сировиною. Проаналізовано зміна жирнокислотного складу січених напівфабрикатів з м’яса птиці при різних рівнях введення та типах модифікованих жирів, обґрунтовано раціональні рівні та форму внесення модифікованих жирів. Проведено порівняльний аналіз змодельованих рецептур з продуктами традиційного асортименту та доведено підвищення біологічної повноцінності продукту.

Meat products are one of basic fat sources in human nutrition. Biological value of fat is determine by PUFA/SFA ratio and omega-6 to omega-3 fatty acids ratio. Biological value of meat half-finished products is low in cause of high polyunsaturated fatty acids intake . With the object to solution of this problem is modi fied fat application perceptively. Main object of this work was to investigate the ability of using mixed fat examples for production of protein –fat emulsion and following producing of half-finished meat products (especially cutlets). For investigation was taken a two kinds of mixed fats – one(A) including the palm oil (7%) , palm oleine (30%) and rape oil (63%); and second (B) including the palm oil (70%), corn oil (25%) and flax oil (5%).Testing examples was distributed to the depend protein – fat emulsion content (20, 22,5 and 25 %). Protein – fat emulsion includes the dry milk whey, pork skin protein, water and far in ratio as – 1:4:15:5. Formulation of cutlets consist of emulsion, poultry meat, pork fat and hydrated dietary fiber. Using the mathematical modeling method and analysis of stuff fatty acid composition it was estimated the theoretical fatty acid composition of modeling recipes. Calculated biological value of modeling recipes was higher than value of control example. The PUFA/ SFA ratio was in gap of 0,34- 0,49 for modeling recipes and 0,84 for control example, that shows the efficiency of modified, poultry and pork fat combination in formulas of minced half-finished meat products.
Modeling of fatty acid composition of poultry meat minced half-finished products with modified fats application
Keywords: органічна хімія; біологічна цінність жиру; клітковина; пальмова олія; half-finished meat products; modified fat; pork fat; protein-fat emulsion; dietary fiber